2014
DOI: 10.6116/kjh.2014.29.6.21.
|View full text |Cite
|
Sign up to set email alerts
|

The anti-inflammatory effect of Taraxacum coreanum on lipopolysaccharide induced inflammatory response on RAW 264.7 cells

Abstract: Objectives : Taraxacum coreanum (TC) have been used as a traditional medicine to treat inflammatory diseases and anti-oxidant effect in Korea. However, the anti-inflammatory effect of TC water extract on lipopolysaccharide (LPS)-induced inflammation is not well-known. Therefore, this study was performed to identify the anti-inflammatory effect of TC on LPS induced inflammatory. Methods : RAW 264.7 cells were treated with 500 ng/mL of LPS. Water extracts of TC (0.1, 0.25, 0.5 mg/ml) was treated 1 h prior to LPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…The seed of Carthamus tinctorius L. (CTS) has been used for studying pharmacological activities, such as anti-inflammation, antioxidation, and anti-diabetes [6,7]. Taraxacum coreanum (TC) has been used for the treatment of inflammatory diseases, such as rheumatic disease and gastritis, for a long time [8][9][10]. Several studies reported the neuroprotective effects of CTS and TC, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The seed of Carthamus tinctorius L. (CTS) has been used for studying pharmacological activities, such as anti-inflammation, antioxidation, and anti-diabetes [6,7]. Taraxacum coreanum (TC) has been used for the treatment of inflammatory diseases, such as rheumatic disease and gastritis, for a long time [8][9][10]. Several studies reported the neuroprotective effects of CTS and TC, respectively.…”
Section: Introductionmentioning
confidence: 99%